2014
DOI: 10.1152/ajpheart.01019.2013
|View full text |Cite
|
Sign up to set email alerts
|

IL-6 regulates adipose deposition and homeostasis in lymphedema

Abstract: Lymphedema (LE) is a morbid disease characterized by chronic limb swelling and adipose deposition. Although it is clear that lymphatic injury is necessary for this pathology, the mechanisms that underlie lymphedema remain unknown. IL-6 is a known regulator of adipose homeostasis in obesity and has been shown to be increased in primary and secondary models of lymphedema. Therefore, the purpose of this study was to determine the role of IL-6 in adipose deposition in lymphedema. The expression of IL-6 was analyze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
65
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 76 publications
(70 citation statements)
references
References 35 publications
2
65
0
3
Order By: Relevance
“…IL-6 is a known regulator of adipose homeostasis in obesity, and is elevated in primary and secondary models of lymphedema. Results in another study demonstrated the expression of IL-6 was associated with adipose deposition and CD4+ inflammation and was markedly decreased in CD4KO mice (224). In addition, loss of IL-6 function resulted in significantly increased adipose deposition after tail lymphatic injury.…”
Section: Obesity Lymphatics and Lymphedemamentioning
confidence: 99%
See 1 more Smart Citation
“…IL-6 is a known regulator of adipose homeostasis in obesity, and is elevated in primary and secondary models of lymphedema. Results in another study demonstrated the expression of IL-6 was associated with adipose deposition and CD4+ inflammation and was markedly decreased in CD4KO mice (224). In addition, loss of IL-6 function resulted in significantly increased adipose deposition after tail lymphatic injury.…”
Section: Obesity Lymphatics and Lymphedemamentioning
confidence: 99%
“…In addition, loss of IL-6 function resulted in significantly increased adipose deposition after tail lymphatic injury. The observations in these studies suggested that IL-6 is increased as a result of adipose deposition and CD4+ cell inflammation in lymphedema and that IL-6 expression in lymphedema acts to limit adipose accumulation (224). …”
Section: Obesity Lymphatics and Lymphedemamentioning
confidence: 99%
“…LVA was performed 5 months after the onset of lymphedema in case 1, whereas more than 5 years had elapsed before LVA was performed in case 2. Accumulation of adipose and fibrous tissue tends to be progressive in patients in lymphedema, which contributes to the increasing size of the affected limb . Therefore, accumulation of adipose and fibrous tissue over a period of 5 years duration would have rendered volume reduction by LVA difficult in case 2.…”
Section: Discussionmentioning
confidence: 99%
“…Accumulation of adipose and fibrous tissue tends to be progressive in patients in lymphedema, which contributes to the increasing size of the affected limb. 11 Therefore, accumulation of adipose and fibrous tissue over a period of 5 years duration would have rendered volume reduction by LVA difficult in case 2. The difference in volume reduction between these two cases underscores the potential importance of performing LVA in the early stage of lymphedema.…”
Section: Differences Between the Two Casesmentioning
confidence: 99%
“…Obesity has been linked with lymphedema risk, development and severity in numerous clinical trials and animal studies (621). While accumulation of adipose tissue is known to be a hallmark of the edematous limb and is seen in nearly all animal models of lymphedema (11, 12, 15, 18, 20), preoperative body-mass-index (BMI) is one of the few predisposing factors for lymphedema that has continuously been demonstrated in clinical trials (6, 13, 14, 16, 17, 19, 21). Utilizing this information coupled with other risk factors that can be easily measured such as elevated blood pressure (17) and the number of lymph nodes removed (6, 8, 22) could provide a powerful tool for identifying those patients most at risk.…”
Section: Patient History and Routine Surveillancementioning
confidence: 99%